2015
DOI: 10.1186/s12903-015-0088-5
|View full text |Cite
|
Sign up to set email alerts
|

Associations between dental anxiety, sense of coherence, oral health-related quality of life and health behaviour – a national Swedish cross-sectional survey

Abstract: BackgroundDental anxiety (DA) is a common condition associated with avoidance of dental care and subsequent health-related and psychosocial outcomes, in what has been described as the vicious circle of DA. Also, recent studies have found an association between the psychosocial concept of sense of coherence (SOC) and DA. More studies are needed to verify the relationship between DA and SOC, especially using population-based samples. There is also a need for studies including factors related to the vicious circl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
93
1
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(117 citation statements)
references
References 42 publications
9
93
1
8
Order By: Relevance
“…This association could be explained by known risk factors that are associated with dental fear, such as irregular dental visits and high numbers of caries. A previous survey conducted among Swedish adults found that dental anxiety was associated with irregular dental care and low OHRQoL [23]. In addition, fearful children (aged 4–11 years old) and fearful preschoolers were reported to have had more caries experience and more avoidance patterns than those without fear [24, 25].…”
Section: Discussionmentioning
confidence: 99%
“…This association could be explained by known risk factors that are associated with dental fear, such as irregular dental visits and high numbers of caries. A previous survey conducted among Swedish adults found that dental anxiety was associated with irregular dental care and low OHRQoL [23]. In addition, fearful children (aged 4–11 years old) and fearful preschoolers were reported to have had more caries experience and more avoidance patterns than those without fear [24, 25].…”
Section: Discussionmentioning
confidence: 99%
“…In New Delhi, the prevalence of dental anxiety ranges between 7.4% and 22.6% for children between ages 3 and 14 years, the consequence the same to a review that prevalence of dental anxiety in youth samples ranges from approximately 5% to 20% . Dental anxiety is a multifactorial phenomenon, caused by three main factors: aversive in the dental office, vicarious learning through role models, and psychodynamic and personality, which can cause children to avoid dental visits and negatively influence the behavior during the course of dental visit, thereby resulting in more teeth decay and gingivitis in future, and this can potentially exacerbate the child's level of dental anxiety . So the dentist plays an important role in decreasing or eliminating dental anxiety in the patient and promoting good general oral hygiene habits …”
Section: Introductionmentioning
confidence: 95%
“…The use of psychometric tests to evaluate health‐related quality of life (HRQoL) and oral health‐related quality of life (OHRQoL) in relation to different health conditions is both adequate and necessary . Patient‐reported outcome measures (PROMS) are currently the key variables used when assessing old and new medical technologies, irrespective of the study design.…”
mentioning
confidence: 99%